Comparison of prevalence of human papillomavirus antigen in biopsies from women with cervical intraepithelial neoplasia. Issue 8 (August 1985) - Singer, A; Wilters, J; Walker, P; Jenkins, D; Slavin, G; Cowdell, H; To, A; Husain, O
Abstract : Human papillomavirus antigen was found in 39 (16%) of 253 colposcopic biopsies from a group of women at high risk for cervical cancer who had been examined in the early 1970s. Immunohistochemical evidence of papillomavirus infection was found in 20 (30%) of 67 cervical intraepithelial neoplasia lesions infected with wart virus from these patients. When these results were compared with results of a similar study carried out in the early 1980s there was no significant difference in the prevalence of human papillomavirus antigen in cervical intraepithelial neoplasia lesions infected with wart virus from women who had been examined over a decade apart.